Identifikasi Keragaman Gen Flavin-Containing Monooxygenases 3 (FMO3|AlwNI) pada Ayam Lokal Indonesia - Suhita, R. L.; Gunawan, A.; Darwati, S.; Ulupi, N.; Sumantri, C. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Local chicken in Indonesia is commonly maintained traditionally for meat consumption so that ithas the potential to be developed as an economical livestock commodities. The increasing of meat local chicken demand should be followed by the increasing of its quality. FMO3 gene as a gene that control meat quality especially controlling fish odor in livestock product, can be used as a functional gene in its function as a genetic marker. This research was aimed to identify the FMO3 gene polymorphism in exon 6 inbroiler, kampung,sentul, merawang, pelung and nunukan chicken population. Identification of polymorphism was used 129 samples from those populations. AlwnIenzyme was used in PCR-RFLP technique to digest PCR product overnight.Genotypingshowed only AA genotype (275/249 bp) in 524 bp product amplification. There was no polymorphism found in every population. It needs further study in the different sequences to findthe polymorphism of FMO3 in local chicken.